Biogeographic assessments: A framework for information synthesis in marine spatial planning. (January 2015) - Caldow, Chris; Monaco, Mark E.; Pittman, Simon J.; Kendall, Matthew S.; Goedeke, Theresa L.; Menza, Charles; Kinlan, Brian P.; Costa, Bryan M.
Abstract: This paper presents the Biogeographic Assessment Framework (BAF), a decision support process for marine spatial planning (MSP), developed through two decades of close collaborations between scientists and marine managers. Spatial planning is a considerable challenge for marine stewardship agencies because of the need to synthesize information on complex socio-ecological patterns across geographically broad spatial scales. This challenge is compounded by relatively short time-frames for implementation and limited financial and technological resources. To address this pragmatically, BAF provides a rapid, flexible and multi-disciplinary approach to integrate geospatial information into formats and visualization tools readily useable for spatial planning. Central to BAF is four sequential components: (1) Planning; (2) Data Evaluation; (3) Ecosystem Characterization; and (4) Management Applications. The framework has been applied to support the development of several marine spatial plans in the United States and Territories. This paper describes the structure of the BAF framework and the associated analytical techniques. Two management applications are provided to demonstrate the utility of BAF in supporting decision making in MSP. Highlights: The Biogeographic Assessment Framework (BAF) supports information-based MSP. It provides a rapid and transparent step-wise process for data synthesis. It provides a clear presentation of data uncertainty for informed decision support. Two case studies illustrate the application of the framework to support MSP. Future directions and priority needs central to effective MSP are highlighted.